2011
DOI: 10.1002/syn.20912
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin1/OrexinA‐containing axons innervate locus coeruleus neurons that project to the Rat medial prefrontal cortex. Implication in the sleep‐wakefulness cycle and cortical activation

Abstract: The Hypocretin1/OrexinA (Hcrt1/OxA) neuropeptides are found in a group of posterolateral hypothalamus neurons and are involved in sleep-wakefulness cycle regulation. Hcrt1/OxA neurons project widely to brainstem aminergic structures, such as the locus coeruleus (LC), which are involved in maintenance of wakefulness and EEG activation through intense projections to the medial prefrontal cortex (mPFC). Moreover, defects of the Hcrt1/OxA system are linked to narcolepsy, a disorder characterized by excessive diurn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 57 publications
3
22
0
Order By: Relevance
“…However, it is unknown, so far, which of these pathways is more relevant for arousal and wakefulness. Our results complement previous studies on Hcrt1/OxA innervation of brainstem wakefulness-related areas, [4951], and allow us to establish cellular and subcellular bases by which the Hypocretinergic/orexinergic system excites VTA neurons that project to PL, activating the cerebral cortex. The VTA is not the only gateway for Hcrt1/OxA neurons to gain acces to the mPFC.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, it is unknown, so far, which of these pathways is more relevant for arousal and wakefulness. Our results complement previous studies on Hcrt1/OxA innervation of brainstem wakefulness-related areas, [4951], and allow us to establish cellular and subcellular bases by which the Hypocretinergic/orexinergic system excites VTA neurons that project to PL, activating the cerebral cortex. The VTA is not the only gateway for Hcrt1/OxA neurons to gain acces to the mPFC.…”
Section: Discussionsupporting
confidence: 87%
“…The common observation of Hcrt1/OxA axons close to blood vessels, similar to what has been reported in other brain areas [4951], suggests an association between the Hcrt/Ox system and vasomotor control. In fact, Hcrt/Ox-R1 activation attenuates neurogenic vasodilation of dural vessels [52].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The LC also receives a dense innervation by Orx varicosities and has a high density of Orx1 receptors (Peyron et al, 1998;Hervieu et al, 2001;Cluderay et al, 2002). Whereas a proportion of the MCH varicosities contained VGAT and abutted gephyrin puncta in the LC here, a proportion of the Orx varicosities contained VGluT2 and contacted PSD-95, the postsynaptic density protein at glutamatergic synapses, in a previous study (Henny et al, 2010) and were also shown to make asymmetric synapses with the noradrenergic neurons (Horvath et al, 1999;Del Cid-Pellitero and Garzon, 2011). Thus the Orx neurons can excite noradrenergic neurons in the LC through excitatory action of their peptide together with that of glutamate to elicit wakefulness (Bourgin et al, 2000;Carter et al, 2010), when both the Orx neurons (Lee et al, 2005;Mileykovskiy et al, 2005) and LC neurons selectively discharge (Aston- Jones and Bloom, 1981).…”
Section: Discussionmentioning
confidence: 58%
“…Early anatomical studies in rat suggested that some brainstem afferents terminate within the LC proper, while most other projections target the Peri-LC (Aston-Jones et al, 1986; Van Bockstaele et al, 2001). In addition it has been demonstrated that some projections from the preoptic and lateral hypothalamic areas, periaqueductal gray, and CAmy target the LC core (Luppi et al, 1995; Lee et al, 2005; Reyes et al, 2011), although some of the lateral hypothalamic hypocretin neurons may target non-noradrenergic LC projection neurons (Del Cid-Pellitero and Garzon, 2011). However, for many afferents it is still not clear whether they target interneurons or dendrites of noradrenergic neurons within the Peri-LC zone.…”
Section: Introductionmentioning
confidence: 99%